Writing for academic journals - Murray, Rowena (Maidenhead, Berkshire, England : Open University Press, 2013)
Busy academics must publish. To fulfil research output, they must write to a specific journal style and high standard while juggling other professional tasks. This book develops understanding of how writing happens, what good writing looks and feels like, what gets published and what does not and why.
Previous edition: 2009.
Includes bibliographical referenes (pages [230]-237) and index.
Keywords: Academic writing